Enriching Women's Poor Political Education - Matroni; Moh. Toyu (Indonesian Journal of Islamic Education and Learning, 2025)
This  research  focuses  on  the  study  of  Islam  from  a  philosophical  perspective  using  a  theoretical  framework. Education  and  the  modern  Islamic  historical  approach  of  Ibrahim  Abu  Rabi',  with  the  aim  of  enriching  the  philosophical  horizon  related  to  contemporary  problems,  namely  women's  education,  while  the  methodology in  this  study  uses  qualitative  methods,  with  the  conclusion  that  to  read  the  problems  of  Islamic  education today,  we  must  open  the  tap  of  modern  Islamic  history  as  the  forerunner  to  the  development  of  Islamic education  today  which  continues  to  experience  change  and  development